Molecular docking study of Zingiber officinale Roscoe compounds as a mumps virus nucleoprotein inhibitor - Viol Dhea Kharisma; Santika Lusia Utami; Wahyu Choirur Rizky; Tim Godefridus Antonius Dings; Md Emdad Ullah; Vikash Jakhmola; Alexander Patera Nugraha (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Mumps virus (MuV) can trigger severe infections, such as parotitis, epididymo-orchitis, and meningitis. The effectiveness of MuV vaccine administration has been proven, but current outbreaks warrant the development of antivirals against MuV. Zingiber officinale var. Roscoe or ginger is often used as an alternative remedy. Currently, there are no known in vitro or in vivo studies that investigate ginger as an MuV antiviral. Purpose: This study aims to evaluate the antiviral potency of the bioactive compounds in Zingiber officinale var. Roscoe against MuV. Methods: Antiviral activity screening was conducted by druglikeness analysis, antiviral probability, molecular docking, and molecular dynamic simulation. Results: As an antiviral, 6-shogaol from Zingiber officinale var. Roscoe has potency against MuV. It has a good binding affinity and can establish interactions with the binding domain of the target protein by forming hydrogen, Van der Waals, and alkyl bonds. Conclusion: The complex of 6-shogaol_NP was predicted to be volatile but stable for triggering inhibitory activity. However, these results must be proved by in vivo and in vitro approaches to strengthen the scientific evidence.